Investigation of Effective factors on reinforcement of Entrepreneurship Moral of agricultural production cooperativs members in Amol Township - F Tavasoli; M Chrmchian Langroodi; A Ahmadpur (تعاون و کشاورزی, 2012)
Undoubtedly،the process of economic development in developing countries،reflects that the economy has afected entrepreneurship.When the entrepreneur is applied to the cooperatives ،it can be hoped that whit cooperatives benefiting from factors such as creativity and innovation،identify the opportunities and risks can in the business environment have created good position.Therefore،the main objective of this study is to investigate of effective factors on entreprenurship morale reinforcement of agricultural production cooperative members in Amol township in 2011-2012.The statistical population included 2029 members of agriculture prodution cooperatives.The sample size was determined 234 using Cochran،s formula. Finally 219 questionnaires were completed through stratified random sampling technique.Research methodology  was a combination of descriptive-analysis the data،SPSS 15 was used. In order to investigate the reliability of research questionnaire،25 agricultural production cooperatives members in Babol were randomly selected that Cronbach،s alpha and ordinal theta were calculated 0.88 and 0.89 respectivety.results of Kendall،s tau correlation coefficient indicate that between paycholigical-personality، socio-culturalفeconomical،educational and reinforcement of entrepreneurship moral is a positive and significant relationship at the one percent level.Also،about 31.6 percent of entrepreneurship morale reinforcement variance was determined  through factors of economical،educational،psychological-personality،institutional.